2020
DOI: 10.21203/rs.3.rs-19741/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Biosurfactant production by Trichoderma sp. MK116452 and its possible application in oil recovery

Abstract: Surfactants are amphiphatic compounds containing both hydrophilic and hydrophobic groups, which are capable of lowering surface or interfacial tension. Considering the advantages of using biosurfactants produced by microorganisms, the aim of this study was to develop and characterise a biosurfactant produced by Trichoderma sp. MK116452 isolated from Seri Chermin filling station, Brunei Darussalam, and to examine its potential application in microbial enhanced oil recovery (MEOR). The microorganism was cultured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…These studies indicated the specific presence of hexadecenoic acid (16:0) and octadecenoic acid (18:0), which correlates with the presented results. Likewise, the FTIR analysis confirmed that the examined biosurfactants are glycolipids [ 29 ].…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…These studies indicated the specific presence of hexadecenoic acid (16:0) and octadecenoic acid (18:0), which correlates with the presented results. Likewise, the FTIR analysis confirmed that the examined biosurfactants are glycolipids [ 29 ].…”
Section: Discussionmentioning
confidence: 78%
“…The presence of the most common extracellular products was mainly detected as: 14:0, 16:0, 18:0, 18:1cis, 18:2trans, 18:2cis, 20:0. In addition, Matussin et al [ 29 ] analyzed the potential of the selected Trichoderma strain towards biosurfactants production in mineral medium with 40 g/L sucrose, but also 2% of crude oil content. These studies indicated the specific presence of hexadecenoic acid (16:0) and octadecenoic acid (18:0), which correlates with the presented results.…”
Section: Discussionmentioning
confidence: 99%